Antifungal Effect of Malaysian Aloe vera Leaf Extract on Selected Fungal Species of Pathogenic Otomycosis Species in In Vitro Culture Medium - Saniasiaya, Jeyasakthy; Salim, Rosdan; Mohamad, Irfan; Harun, Azian (Oman Medical Specialty Board, 2017)
Objectives: Aloe barbadensis miller or Aloe vera has been used for therapeutic purposes since ancient times with antifungal activity known to be amongst its medicinal properties. We conducted a pilot study to determine the antifungal properties of Malaysian Aloe vera leaf extract on otomycosis species including Aspergillus niger and Candida albicans. Methods: This laboratory-controlled prospective study was conducted at the Universiti Sains Malaysia. Extracts of Malaysian Aloe vera leaf was prepared in ethanol and solutions via the Soxhlet extraction method. Sabouraud dextrose agar cultured with the two fungal isolates were inoculated with the five different concentrations of each extract (50 g/mL, 25 g/mL, 12.5 g/mL, 6.25 g/mL, and 3.125 g/mL) using the well-diffusion method. Zone of inhibition was measured followed by minimum inhibitory concentration (MIC). Results: For A. niger, a zone of inhibition for alcohol and aqueous extract was seen for all concentrations except 3.125 g/mL. There was no zone of inhibition for both alcohol and aqueous extracts of Aloe vera leaf for C. albicans. The MIC values of aqueous and alcohol extracts were 5.1 g/mL and 4.4 g/mL for A. niger and since no zone of inhibition was obtained for C. albicans the MIC was not determined. Conclusions: The antifungal effect of alcohol extracts of Malaysian Aloe vera leaf is better than the aqueous extract for A. niger (p < 0.001). Malaysian Aloe vera has a significant antifungal effect towards A. niger.